Evaluasi Implementasi “POMP” Filariasis Dan Faktor Yang Berhubungan Dengan Permasalahannya Di Kabupaten Manggarai Timur Tahun 2017 - FRANSISKUS SALESIUS ONGGANG (JURNAL INFO KESEHATAN, 2017)
Filariasis is a chronic infectious disease caused by filarial worms and is transmitted by Mansonia, Anopheles, Culex, Armigeres mosquitoes. The worms live in the lymph and lymph nodes with acute clinical manifestations of recurrent fever, inflammation of the lymph node ducts. This disease is one of the serious public health problems in Indonesia. Almost all areas of Indonesia are filariasis-endemic areas, especially in eastern Indonesia which has a higher prevalence. Mass filariasis should be evaluated for the sustainability of the treatment program for the following year so as to find an efficient and effective treatment model. The purpose of this study is to evaluate the implementation of filariasis POMP and factors related to its success in East mangarai regency of 2017. The location of this research is conducted in East Manggarai Regency. This research uses qualitative approach and using mixed method in which to see the success of mass treatment in East manggarai Regency. Variables in this study For data collection techniques in this study is done in several ways each variable. Data analysis using univariate analysis. Data collected, processed and analyzed descriptively with qualitative analytical approach. The results of this study indicate that the implementation of POMF treatment Implementation of filariasis treatment with 83% results, the problem of treatment of filariasis POMP treatment in East Manggarai Regency in 2017 is uneven distribution of anti-filariasis drugs, incomplete monitoring of drug side effects post-treatment of mass, received drugs are not complete, incomplete treatment frequency for two mass treatments in 2016 and 2017, and has not received support from the legislature in filariasis mass treatment budgeting in East Manggarai District.